Temporal constraints on future accumulation-area loss of a major Arctic ice cap due to climate change (Vestfonna, Svalbard) - Möller, Marco; Schneider, Christoph (RWTH Aachen University, 2015)
Scientific reports 5, 8079 (2015). doi:10.1038/srep08079 : Published by Nature Publishing Group, London